Genome-wide association scan in north Indians reveals three novel HLA-independent risk loci for ulcerative colitis. Issue 4 (16th May 2014) - Juyal, Garima; Negi, Sapna; Sood, Ajit; Gupta, Aditi; Prasad, Pushplata; Senapati, Sabyasachi; Zaneveld, Jacques; Singh, Shalini; Midha, Vandana; van Sommeren, Suzanne; Weersma, Rinse K; Ott, Jurg; et al.
Abstract : Objective: Over 100 ulcerative colitis (UC) loci have been identified by genome-wide association studies (GWASs) primarily in Caucasians (CEUs). Many of them have weak effects on disease susceptibility, and the bulk of the heritability cannot be ascribed to these loci. Very little is known about the genetic background of UC in non-CEU groups. Here we report the first GWAS on UC in a genetically distinct north Indian (NI) population. Design: A genome-wide scan was performed on 700 cases and 761 controls. 18 single-nucleotide polymorphisms (SNPs) (p<5×10 −5 ) were genotyped in an independent cohort of 733 cases and 1148 controls. A linear mixed model was used for case–control association tests. Results: Seven novel human leucocyte antigen (HLA)-independent SNPs from chromosome 6, located in 3.8-1, BAT2, MSH5, HSPA1L, SLC44A4, CFB and NOTCH4, exceeded p<5×10 −8 in the combined analysis. To assess the independent biological contribution of such genes from the extended HLA region, we determined the percentage alternative pathway activity of complement factor B ( CFB ), the top novel hit. The activity was significantly different (p=0.01) between the different genotypes at rs12614 in UC cases. Transethnic comparisons revealed a shared contribution of a fraction of UC risk genes between NI and CEU populations, in addition to genetic heterogeneity. Conclusions: This study shows varying contribution of the HLA region to UC in different populations. Different environmental exposures and the characteristic genetic structure of the HLA locus across ethnic groups collectively make it amenable to the discovery of causative alleles by transethnic resequencing. This may lead to an improved understanding of the molecular mechanisms underlying UC.